Model validation for a noninvasive arterial stenosis detection problem - H. Thomas Banks; Shuhua Hu; Zackary R. Kenz; Carola Kruse; Simon Shaw; John Whiteman; Mark P. Brewin; Stephen E. Greenwald; Malcolm J. Birch (Mathematical Biosciences and Engineering)
A current thrust in medical research is the development of a non-invasive method for detection, localization, and characterization of an arterial stenosis (a blockage or partial blockage in an artery). A method has been proposed to detect shear waves in the chest cavity which have been generated by disturbances in the blood flow resulting from a stenosis. In order to develop this methodology further, we use one-dimensional shear wave experimental data from novel acoustic phantoms to validate a corresponding viscoelastic mathematical model. We estimate model parameters which give a good fit (in a sense to be precisely defined) to the experimental data, and use asymptotic error theory to provide confidence intervals for parameter estimates. Finally, since a robust error model is necessary for accurate parameter estimates and confidence analysis, we include a comparison of absolute and relative models for measurement error.